Those dynamic years 1930-31-32 - DEMARIA G., G. (PSL Quarterly Review, 2013)
The paper is a contribution to a series of recollections and reflections on the professional experiences of distinguished economists which the Banca Nazionale del Lavoro Quarterly Review started in 1979. In it Giovanni Demaria looks back on a period of particular significance for his professional life after obtaining the first scholarship from the Rockefeller Foundation to Italy. JEL: B31